The Anticancer Activity of Ethanol Extract of Begonia medicinalis on Colorectal Cancer Rat Model Induced With 7,12-Dimethylbenz[A]Anthracene - Guli, Musjaya; Ardiputra, Muh Akbar; Pitopang, Ramadanil; Sari, Retno; Hatta, Mochammad; Prawiro, Sumarno Reto; Saifah, Andi; Sardi, Bambang; Rahma, Rahma; Rahmawati, Nurul Dina (Media Publikasi Cendekia Indonesia, 2025)
Colorectal cancer remains one of the leading causes of cancer-related deaths after lung cancer, highlighting the urgent need for more effective therapies with minimal side effects. Begonia medicinalis has been reported to have potential anticancer properties. This study aimed to evaluate the anticancer activity of Begonia medicinalis extract by assessing neutrophil concentration in a 7,12-dimethylbenz[a]anthracene (DMBA)-induced colorectal cancer rat model. The research employed a laboratory-based experimental approach with a post-test-only group design, comprising five groups with five replications each: treatment group I receiving a 25 mg/kg body weight, treatment group II receiving a 50 mg/kg body weight, treatment group III receiving a 100 mg/kg body weight, an normal group that was not DMBA-induced and did not receive therapy, and a negative control group that was DMBA-induced but did not receive therapy. The results of this study demonstrate that Begonia medicinalis extract effectively suppresses neutrophil concentration in a DMBA-induced colorectal cancer rat model. Treatment with 50 mg/kg body weight and 100 mg/kg body weight doses successfully reduced neutrophil cell levels in the experimental subjects, with the best results seen at the 100 mg/kg body weight dosage. This study provides new insights into the effects of plant-based therapies, Begonia medicinalis extract, in modulating the immune system by suppressing neutrophil concentration in a colorectal cancer rat model.